Organizational Commitment as Mediating Organizational Culture and Work Engagement on Performance - Novalien Carolina Lewaherilla; Gerrit Mathias Pentury; Rachma Atamimi; Asiani Sijabat (Enrichment : Journal of Management, 2022)
This study aims to analyze the influence of organizational culture, work involvement, commitment and its influence on employee performance. The samples taken were all employees of the Ambon State Christian Institute of 60 respondents. The results of this study indicate that: (1) organizational culture has a positive and significant effect on organizational commitment, (2) work involvement has a positive and significant effect on organizational commitment, (3) organizational culture has a positive and significant effect on employee performance, (4) engagement work does not have a positive and significant effect on employee performance, (5) organizational commitment has a positive and significant effect on employee performance. (6) Organizational culture influences performance with organizational commitment as a mediating variable.